ORGANIZATION OF MEALS FOR PATIENTS WITH CORONAVIRUS INFECTION IN A RE-PROFILED INFECTIOUS DISEASES HOSPITAL - Ликстанов, Михаил Исаакович; Бахтина, Наталья Валерьевна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна (Medicine in Kuzbass, 2020)
The article presents the experience of organizing meals for patients with coronavirus infection in the conditions of a redesigned covid hospital